Special Features of the Structure of Copper-containing Products of Plasma Dynamic Synthesis; Russian Physics Journal; Vol. 57, № 11 - Ivashutenko A. S. Alexander Sergeevich; Nazarenko O. B. Olga Bronislavovna; Sivkov A. A. Aleksandr Anatolyevich; Saigash A. S. Anastasiya Sergeevna; Stepanov K. I. Kirill Igorevich (2015, 2015)
Title screen